Stable weak approximation at work in index-linked catastrophe bond pricing - Krzysztof Burnecki; Mario Nicoló Giuricich (Risks, 2017)
We consider the subject of approximating tail probabilities in the general compound renewal process framework, where severity data are assumed to follow a heavy-tailed law (in that only the first moment is assumed to exist). By using the weak convergence of compound renewal processes to a-stable Lévy motion, we derive such weak approximations. Their applicability is then highlighted in the context of an existing, classical, index-linked catastrophe bond pricing model, and in doing so, we specialize these approximations to the case of a compound time-inhomogeneous Poisson process. We emphasize a unique feature of our approximation, in that it only demands finiteness of the first moment of the aggregate loss processes. Finally, a numerical illustration is presented. The behavior of our approximations is compared to both Monte Carlo simulations and first-order single risk loss process approximations and compares favorably.
Keywords: 330; index-linked catastrophe bonds; compound renewal process; compound Poisson process; heavy-tailed claims; table Lévy motion; weak convergence